Family Working Time Integration of Bali Cattle and Rice Field in South Konawe Regency to Increase Family Income - Musram Abadi; La Ode Arsad Sani; La Ode Muh. Munadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to determine the availability and employment of the work time of family labor in Bali cattle farming integration of rice field farming in Tinanggea District, South Konawe Regency. The location of the research is determined intentionally (purposive sampling) in consideration of the Tinanggea District area is the area of cattle breeding center of Bali. The research population will be selected 6 villages based on the number of livestock populations and there are rice fields. The number of respondents per village was 5 to the number of respondents as many as 30 respondents. The respondent determination of each selected village is done in Simple Random Sampling. Based on the results of the study can be concluded that the average pouring time of family labor at the Bali cattle business of 0.92 HOK, while the average time spent on family labor in the farm rice field of 10.55 HOK. In general, the family workforce in Tinanggea District, South Konawe Regency is quite available with more time on rice farming (91.98%) Compared to the Bali cattle farming (8.02%).